Diagnostic value of CT enhancement degree in lymph node metastasis of papillary thyroid cancer: A comparison of enhancement, ratio, and difference - Zhu, Jiying; Tian, Min; Zhang, Tong; Zhu, Hanlin; Wei, Peiying; Han, Zhijiang (Frontiers in Endocrinology, 2023)
Objectives: To evaluate the value of computed tomography (CT) enhancement degree in diagnosing lymph node (LN) metastasis in papillary thyroid carcinoma (PTC) by determining the ratio and difference between the Hounsfield units (HU) of CT enhancement and plain scan of the LNs, as well as between the HU of CT-enhanced LNs and the sternocleidomastoid muscle. Methods: The plain and enhanced CT findings of 114 metastasis-positive LNs in 89 cases and 143 metastasis-negative LNs in 114 cases of PTC were analyzed retrospectively. Plain HU of LNs (PNHU), enhanced HU of LNs (ENHU) , and enhanced HU of the sternocleidomastoid muscle (EMHU) were measured. The ENHU, difference between ENHU and PNHU (EN-PNHU), ratio of ENHU to PNHU (EN/PNHU), difference between ENHU and EMHU (EN-EMHU), and ratio of ENHU to EMHU (EN/EMHU) in metastasis-positive and metastasis-negative LN groups were calculated, the corresponding diagnostic efficacy for differentiating metastasis-positive from metastasis-negative LNs in PTC were sought using the receiver-operating curve. The interobserver agreement between readers was assessed using the interobserver correlation coefficient (ICC). Results: The ENHU of 114 metastasis-positive LNs and 143 metastasis-negative LNs was 113.39 ± 24.13 and 77.65 ± 15.93, EN-PNHU was 65.84 ± 21.72 HU and 34.07 ± 13.63 HU, EN/PNHU was 2.36 (1.98, 2.75) and 1.76 (1.54, 2.02), EN-EMHU was 49.42 ± 24.59 HU and 13.27 ± 15.41 HU, and EN/EMHU was 1.79 ± 0.40 and 1.21 ± 0.24, respectively (all P < 0.001). The area under the curve, cutoff value, sensitivity, specificity, and accuracy of ENHU for identifying metastasis-positive and metastasis-negative LNs were 0.895, 97.3 HU, 0.746, 0.895, and 0.829, EN-PNHU was 0.894, 47.8 HU, 0.807, 0.874, and 0.844, EN/PNHU was 0.831, 1.9, 0.877, 0.650, and 0.751, EN-EMHU was 0.890, 26.4 HU, 0.807, 0.839, and 0.825, and EN/EMHU was 0.888, 1.5, 0.728, 0.902, and 0.825, respectively. The readers had an excellent interobserver agreement on these five parameters (ICC = 0.874–0.994). Conclusion: In the preoperative evaluation of LN metastasis in PTC, ENHU, EN-PNHU, EN-EMHU, and EN/EMHU had similarly high diagnostic efficacy, with ENHU, EN-PNHU, and EN/EMHU having higher specificity and EN-PNHU and EN-EMHU having higher sensitivity.